Close contacts and noncovalent interactions in crystals. (21st July 2017) - Murray, Jane S.; Resnati, Giuseppe; Politzer, Peter
Abstract : Close contacts, defined as interatomic separations less than the sum of the respective van der Waals radii, are commonly invoked to identify attractive nonbonded interactions in crystal lattices. While this is often effective, it can also be misleading because (a) there are significant uncertainties associated with van der Waals radii, and (b) it may not be valid to attribute the interactions solely to specific pairs of atoms. The interactions within crystal lattices are Coulombic, and the strongest positive and/or negative regions do not always correspond to the positions of atoms; they are sometimes located between atoms. Examples of both types are given and discussed, focusing in particular upon σ-hole interactions.